1983
DOI: 10.1093/nar/11.5.1295
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency polyoma DNA transfection of chloroquine treated cells

Abstract: Chloroquine treatment of rodent cells during the first hours of polyoma DNA transfection increase the fraction of cells expressing viral functions. The effect has been observed after DNA absorption using both the DEAE-dextran and calcium phosphate coprecipitation methods. Exposure to chloroquine increased the proportion of transfected mouse cells to approximately 40%. From a culture of one million such cells, microgram quantities of newly synthesized viral DNA could be isolated. Similarly, the transformation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
301
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 693 publications
(312 citation statements)
references
References 28 publications
11
301
0
Order By: Relevance
“…We found that TAT-pK-mediated gene transfer is affected by either of these agents, suggesting that transduction relies on the endocytic pathway. These results are similar to past reports showing that gene transfer via receptor-mediated endocytosis (Cotten et al, 1990) or mediated by DEAE-dextran (Luthman and Magnusson, 1983) is markedly enhanced with endosomotrophic agents, such as chloroquine. However, our data contradict other studies on TAT-peptide-mediated protein transduction (Mann and Frankel, 1991;Derossi et al, 1996;Vivès et al, 1997;Elliott and O'Hare, 1997) and TAT-phage-mediated gene transfer (Eguchi et al, 2001) that do not depend on endosomotrophic reagents.…”
Section: Discussionsupporting
confidence: 92%
“…We found that TAT-pK-mediated gene transfer is affected by either of these agents, suggesting that transduction relies on the endocytic pathway. These results are similar to past reports showing that gene transfer via receptor-mediated endocytosis (Cotten et al, 1990) or mediated by DEAE-dextran (Luthman and Magnusson, 1983) is markedly enhanced with endosomotrophic agents, such as chloroquine. However, our data contradict other studies on TAT-peptide-mediated protein transduction (Mann and Frankel, 1991;Derossi et al, 1996;Vivès et al, 1997;Elliott and O'Hare, 1997) and TAT-phage-mediated gene transfer (Eguchi et al, 2001) that do not depend on endosomotrophic reagents.…”
Section: Discussionsupporting
confidence: 92%
“…Activity Assays All expression constructs were transfected into COS-7 cells using a DEAE-dextran procedure as modified by Luthman and Magnusson (1983). After 2-3 days, conditioned media from these cultures were applied to 5-day-old triplkate cultures of chick myotubes for 14-20 hr.…”
Section: Methodsmentioning
confidence: 99%
“…[14][15][16] FACS analysis for EGFP expression in these cells indicated that exposure to chloroquine increased the transient expression from 12 to 50% (Figure 2b). However, after selection with G418 for stably expressing hMSCs, only one colony was visualized on one plate.…”
Section: Electroporation Of Mscs a Peister Et Almentioning
confidence: 99%